The Natural History of BK Polyomavirus and the Host Immune Response After Stem Cell Transplantation. (18th December 2019) - Laskin, Benjamin L; Denburg, Michelle R; Furth, Susan L; Moatz, Taylor; Altrich, Michelle; Kleiboeker, Steve; Lutzko, Carolyn; Zhu, Xiang; Blackard, Jason T; Jodele, Sonata; Lane, Adam; Wallace, Gregory; et al.
Abstract: Background: BK polyomavirus (BKPyV) is associated with symptomatic hemorrhagic cystitis after hematopoietic cell transplantation (HCT). Little is known about the host immune response, effectiveness of antiviral treatment, or impact of asymptomatic replication on long-term kidney function. Methods: In children and young adults undergoing allogeneic HCT, we quantified BKPyV viruria and viremia (pre-HCT and at Months 1–4, 8, 12, and 24 post-HCT) and tested associations of peak viremia ≥10 000 or viruria ≥10 9 copies/mL with estimated kidney function (glomerular filtration rate, eGFR) and overall survival at 2 years posttransplant. We examined the factors associated with viral clearance by Month 4, including BKPyV-specific T cells by enzyme-linked immune absorbent spot at Month 3 and cidofovir use. Results: We prospectively enrolled 193 participants (median age 10 years) and found that 18% had viremia ≥10 000 copies/mL and 45% had viruria ≥10 9 copies/mL in the first 3 months post-HCT. Among the 147 participants without cystitis (asymptomatic), 58 (40%) had any viremia. In the entire cohort and asymptomatic subset, having viremia ≥10 000 copies/mL was associated with a lower creatinine/cystatin C eGFR at 2 years post-HCT. Viremia ≥10 000 copies/mL was associated with a higher risk of death (adjusted hazard ratio, 2.2; 95% confidence interval, 1.1–4.2). Clearing viremia was associated with detectable BKPyV-specific T cells and having viremia <10 000 copies/mL, but not cidofovir exposure. Conclusions: Screening for BKPyV viremia after HCT identifies asymptomatic patients at risk for kidney disease and reduced survival. These data suggest potential changes to clinical practice, including prospective monitoring for BKPyV viremia to test virus-specific T cells to prevent or treat BKPyV replication. Abstract : BK polyomavirus (BKPyV) viremia, whether symptomatic or not, is associated with morbidity and mortality after hematopoietic cell transplantation. Detectable BKPyV-specific T cells, but not cidofovir, are associated with clearance of viremia. This suggests potential benefits in screening for asymptomatic viremia.